SUCCESS OF GLABROUS SPLIT THICKNESS SKIN GRAFT FOR SOFT TISSUE DEFECTS OF PALMAR ASPECT OF HANDS: A CONCEPT OF REPLACING HISTOLOGICALLY SAME TISSUE. - MUFASSAR NISHAT; FAIZA IRSHAD; MUHAMMAD UMAR (Journal of University Medical & Dental College, 2018)
ABSTRACT: BACKGROUND: Hands (palmar aspect) and the feet (plantar aspect) have glabrous skin which has special concerns. OBJECTIVE: To determine success of glabrous split thickness skin graft from sole of foot in terms of graft take and color match for soft tissue defects of palmar aspect of hand. METHODS: In this study forty ﬁve patients having soft tissue defects of hand (palmar aspect) were selected. After informed consent, demographic data (name, age, sex, address) and size of defect were recorded. Patients underwent surgery with glabrous split thickness skin grafting on their thpalmar aspects of hand in general anaesthesia. The patients were then followed up at 5 day, 2 weeks, 1 month and 2 months to determine the cosmetic outcome, deﬁned as color match which was either Normal (close to palmar skin) or Hyper pigmented (close to dorsum skin). Finally success was considered yes if graft take was > 85%. RESULTS: The graft take observed at the end of 2 weeks post operatively was more than 85% in 40 patients (88.9%) and less than 85% in 5 patients (11.1%).The normal color match as compared to surrounding skin observed at the end of 2 months post operatively was 100% in those patients where graft take was complete (>85%). The procedure was successful in 40 patients (88.9%). CONCLUSION: The results of this study revealed that glabrous split thickness skin graft for coverage of soft tissue defects of hand (palmar aspect) was successful. The concept of replacing histologically same tissue was correct.